Mechanisms and Impact of Rhizosphere Microbial Metabolites on Crop Health, Traits, Functional Components: A Comprehensive Review - Qingxia Chen; Yingjie Song; Yuxing An; Yinglin Lu; Guohua Zhong (Molecules)
Current agricultural practices face numerous challenges, including declining soil fertility and heavy reliance on chemical inputs. Rhizosphere microbial metabolites have emerged as promising agents for enhancing crop health and yield in a sustainable manner. These metabolites, including phytohormones, antibiotics, and volatile organic compounds, play critical roles in promoting plant growth, boosting resistance to pathogens, and improving resilience to environmental stresses. This review comprehensively outlines the mechanisms through which rhizosphere microbial metabolites influence crop health, traits, functional components, and yield. It also discusses the potential applications of microbial secondary metabolites in biofertilizers and highlights the challenges associated with their production and practical use. Measures to overcome these challenges are proposed, alongside an exploration of the future development of the functional fertilizer industry. The findings presented here provide a scientific basis for utilizing rhizosphere microbial metabolites to enhance agricultural sustainability, offering new strategies for future crop management. Integrating these microbial strategies could lead to increased crop productivity, improved quality, and reduced dependence on synthetic chemical inputs, thereby supporting a more environmentally friendly and resilient agricultural system.